Family Leadership and Small to Medium Sized Enterprises Research and Development Investments - Li, Zhichuan (International Journal of Business, Economics and Management, 2019)
Family businesses are the most widespread and ancient of all economic entities, and the vast majority of small to medium-sized enterprises (SMEs) in every country re family owned. In consequence, their innovation and productivity are critical to economic growth. However, current academic research tends to focus on large, high-profile corporations, with few studies of SMEs. Further, the relationship between family leadership and SMEs’ innovation capability has been likewise neglected. This study aims to investigate the effects of family leadership on an enterprise’s investment in innovation within the context of small firms based on the European Firms in a Global Economy (EFIGE) survey data and relavent literature. By utilizing the ordinary least squares (OLS) model with several robust checks, the empirical results indicate that innovation investment behavior is more complex and multifaceted with respect to family leadership and firm size. On the one hand, family Chief Executive Officers (CEOs) generally exhibit a greater performance in innovation than non-family CEOs. On the other, family leaders in small firms do conduct less innovation investment.